Movimentos de giro no olhar sobre tornar-se velho/a: uma experiência de formação sobre o ensino de língua inglesa para/com pessoas 60+ - (:unkn) unknown (Universidade Estadual de Goiás, 2021)
In this master’s thesis, entitled “Looking otherwise into becoming old: a teacher education experience of English language teaching to/with 60+ people”, Idiscuss the meanings of being old in Brazil and of English language teaching to/with +60 people that are constructed in a teacher education course with fourteen undergraduate students from“English60+” course with three students (research A) and in a Letras course (B.A. in language teaching) at the State University of Goiás (research B),interweaving both studies.Thus, the specific objectives of this study are the following: a) to discuss the perceptions of the agents in relation to the old subject, ageism, and aging; b) to analyze English language teaching activities designed for/with 60+ people, produced by the student teachers; and c) to reflect on the undergraduates’ perceptions of this teacher education experience. This research is guided by the qualitative and interpretative approach (DENZIN; LINCOLN, 2013), by using the following sources for the generation of empirical material: initial questionnaire; study guidelines; virtual meeting (recorded in audio and video and later transcribed), chat on Zoom; teaching activities; final feedback and conversations about the “English60+” course (recorded in audio and later transcribed). The epistemologies on which this study is grounded are decolonial thinking (KRAMSCH, 2019; MALDONADO-TORRES, 2007; SIVESTRE, 2017; SILVESTRE; SABOTA; PEREIRA, 2020; WALSH, 2013, 2018, among others), research on aging and what it means to be old in society (AGUIAR, 2018; BEAUVOIR, 1970; BOSI, 1979; GOLDENBERG, 2020; KRENAK, 2020; LIMA, 2020, among others), and about language teaching aimed at old people (CONCEIÇÃO, 1999; FRANK, 2010; GUIMARÃES, 2006; MURPHY; EVANGELOU, 2016; PIZZOLATTO, 1995, 2008; TAVARES; MENEZES, 2020, among others). This study and analysis of the empirical material gesture towards what I call “looking otherwise”, which concerns attempts of a serpentine movement that seeks to get to know-with, work with people’s agency, stimulate an active posture, and provide other ways of being/living together with the agents of this research. In this respect, this study sought to promote new alternatives by means of a different way of seeing (SILVESTRE; SABOTA; PEREIRA, 2020) in order to open spaces to discuss issues concerning aging, pandemic, and ageism, as well as possibilities of English language teaching to/with 60+ students. With regard to social perceptions of being old, this investigation indicates that the agents changed their perceptions of old age and could envision possibilities and strategies for teaching English to/with 60+ students, which had not been previously considered. Thus, this research contributed to the reflection and understanding of the need to include old people in the curricula of the Letras course (B.A. in language education) – recognizing them as subjects with rights – and it also contributed to supporting the encouragement of efforts aimed a more inclusive teaching.
Looking otherwise into becoming old: a teacher education experience of English language teaching to/with 60+ people
Keywords: Língua inglesa - Terceira idade; Envelhecimento; Formação docente; Deocolonialidade; Idoso; English language; Aging; Teacher education; Decoloniality; CIENCIAS HUMANAS::EDUCACAO